The future(s) of digital agriculture and sustainable food systems: An analysis of high-level policy documents - Lajoie-O'Malley, Alana; Bronson, Kelly; van der Burg, Simone; Klerkx, Laurens (Ecosystem services, 2020)
•Ecosystem services delivery is influenced by food systems and vice versa.•Digitalization of food production has ecosystem, social and ethical impacts.•Frame analysis of policy documents on digital agriculture from World Bank, FAO, OECD.•Dominant narrative which supports the status quo global industrial food system.•Need to think critically about digitalization narratives favouring maximum output. Ecosystem services delivery is influenced by food systems and vice versa. As the application of digital technologies in agriculture continues to expand, digital technologies might affect the delivery of ecosystem services in view of the sorts of food systems in which they are embedded. The direction food systems develop towards the future, and the role digital technologies play in this development, is influenced by imaginings, hopes and visions about what these technologies mean for future food systems. In this article, we investigate what roles are being imagined for these technologies by international actors with the ability to influence the future of food systems. We analyze outward-facing policy documents as well as conference proceedings on digital agriculture produced by the World Bank, the UN Food and Agriculture Organisation (FAO), and the Organisation for Economic Cooperation and Development (OECD). Using qualitative textual analysis, we show that these organisations envision future food systems that prioritize maximizing food output through technology. We illustrate how this vision reflects a long-standing narrative about the role of technology in food systems innovation, which makes the controversial assumption that increases in food production lead to improvements in food security. Based on this finding, we suggest that evaluations of how digital agricultural technologies might affect the delivery of ecosystem services must begin by considering what visions of future food systems are take into account in science, technology development and policy making. Supporting similar research on high-level narratives surrounding agroecology and climate smart agriculture, we find that the dominant narrative in our dataset supports thestatus quoglobal, industrial agriculture and food system. This system continues to be criticized by many scholars for its environmental impacts. Based on our findings, we suggest that ecosystems service researchers could contribute substantially to the evaluation of environmental impacts of digital agriculture by analyzing the impact digital agriculture may have on the trade-offs between provisioning, regulatory, and cultural ecosystem services for several different food system futures. Such analyses can feed into processes of responsible innovation.